2014
DOI: 10.29079/vol13iss2art300
|View full text |Cite
|
Sign up to set email alerts
|

Babesiosis of small ruminants in Sulaimani city Kurdistan – Iraq

Abstract: Babesiosis was studied in sheep and goats in Sulaimani city, Kurdistan -Iraq from June to September 2012. A total of 160 blood samples (135 of sheep and 25 of goats) were collected from different farms. Giemsa stained blood smears were applied to study babesiosis, also ticks were collected from external animals body surfaces. Results of this study showed that Babesia species was recorded among the small ruminants as 92/160 (57.5 %), 76/135 (56.3%) of these from sheep and 16/25 (64%) of goats. Statistically the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…During current survey PCR detected 69.8% prevalence which was higher so far within and outside Pakistan. The results of higher prevalence are in agreement with findings from Egypt [20], Iran [21,22] and Iraq [23] where up to 57% prevalence of Babesia in sheep has been reported. But contrary to present study, lower prevalence as low as just 5% was studied in Iran [21,24,25], Tunisia [26] and Turkey [27].…”
Section: Introductionsupporting
confidence: 91%
“…During current survey PCR detected 69.8% prevalence which was higher so far within and outside Pakistan. The results of higher prevalence are in agreement with findings from Egypt [20], Iran [21,22] and Iraq [23] where up to 57% prevalence of Babesia in sheep has been reported. But contrary to present study, lower prevalence as low as just 5% was studied in Iran [21,24,25], Tunisia [26] and Turkey [27].…”
Section: Introductionsupporting
confidence: 91%
“…The disease is characterized by high temperature, anemia, restlessness, anorexia, and death. Babesiosis is seen in domestic animals, including sheep and goats, however the major economic impact of this infection is on the livestock industry worldwide due to high losses [ 231 , 250 , 266 ]. Babesiosis was investigated in blood samples of sheep and goats in Kurdistan-Iraq from June to September 2012 and four Babesia species were detected: B. ovis, B. motasi, B. foliata, and B. taylori .…”
Section: Tick-borne Diseasesmentioning
confidence: 99%
“…Babesiosis was investigated in blood samples of sheep and goats in Kurdistan-Iraq from June to September 2012 and four Babesia species were detected: B. ovis, B. motasi, B. foliata, and B. taylori . One species of tick vector H. anatolicum was found on these animals [ 231 ]. Babesia spp.…”
Section: Tick-borne Diseasesmentioning
confidence: 99%
“…As well as, our result partially agreed with Sulaiman et al (2010) in Mosul, who showed that the rate of infection was 15.4% from a total 175 goat and Iqbal et al (2011) revealed that the infection rate 16 (24%). However, disagreed with Abdullah and Mohammed (2014), who showed that, the rate of infection 16/25 (64%) from a total of 25 goats in Sulaimani city. Furthermore, Naderi et al (2017), in Iran, explained from a total of 51 sample 9 (2.3%) goats were infected.…”
Section: Discussionmentioning
confidence: 81%
“…Classically microscopic examination of Giemsa-stained blood smears is used to detect Babesia infections (Abdullah andMohammed, 2014 andEsmaeilnejad et al, 2015). However, this method has a low sensitivity and requires expertise because these parasites have similar morphology and therefore, different species may be confused (Bilgic et al, 2017 andGholamreza et al, 2017).…”
Section: Discussionmentioning
confidence: 99%